2015
DOI: 10.1111/jnc.13359
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis toxin reduces calcium influx to protect ischemic stroke in a middle cerebral artery occlusion model

Abstract: Increased calcium influx secondary to glutamate induced excitotoxicity initiates and potentiates devastating pathological changes following ischemic stroke. Pertussis toxin (PTx), a Gprotein blocker, is known to suppress intracellular calcium accumulation. We hypothesize that PTx can protect against stroke by blocking calcium influx. In a permanent middle cerebral artery occlusion model, PTx (1000 ng) was given intraperitoneally 30 min after inducing stroke. Magnetic Resonance Imaging of perfusion and T2-weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…The need for developing an effective and safe treatment for acute stroke remains urgent. The pathogenesis of ischemic stroke is not fully understood; several underlying mechanisms have emerged such as excitotoxicity 4 , oxidative stress 5 , and calcium overload 6 , inflammation and apoptosis 7, 8 . Of these, calcium overload is regarded as the final common pathway of the mechanisms leading to neuronal death 9, 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The need for developing an effective and safe treatment for acute stroke remains urgent. The pathogenesis of ischemic stroke is not fully understood; several underlying mechanisms have emerged such as excitotoxicity 4 , oxidative stress 5 , and calcium overload 6 , inflammation and apoptosis 7, 8 . Of these, calcium overload is regarded as the final common pathway of the mechanisms leading to neuronal death 9, 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Scale bar = 100 μm Previous studies showed that a rise of calcium concentration signals an increased cellular energy demand and mediates a number of pathways that can precipitate mitochondrial injury and cell death [9]. Of interest, increments in [Ca 2+ ] c are detected at the acute phases after MCAO [10][11][12]. At approximately the same time, the expression of MCU is up-regulated [13].…”
Section: Discussionmentioning
confidence: 94%
“…Neurological deficit assessments were performed by investigators who were blinded to the experimental groups, as described previously (Tang et al, 2015 ; Yin et al, 2015 ; Xie et al, 2018 ). Briefly, rating scale was used as follows: score 0 was defined as the complete absence of neurological deficit; score 1 was defined as that front paws incompletely extended and mild neurological deficit; score 2 was defined as lateral turning while walking and moderate neurological deficits; score 3 was defined as lateral jumping of animal body and severe neurological deficits; score 4 was defined as lack of “conscious” response to noxious stimuli.…”
Section: Methodsmentioning
confidence: 99%
“…PTX is used to prepare mouse model of experimental autoimmune encephalomyelitis (EAE; Tang et al, 2013 ). We previously found that low dose of PTX (50 ng/ml) may reduce neuronal calcium influx, thus minimizing neuronal damage and protecting cell viability in stroke (Tang et al, 2015 ). Although PTX, at least at a restricted dose, offers a direct protective effect on neuron, their potential pharmacologic mechanism in stroke protection may include additional key steps.…”
Section: Introductionmentioning
confidence: 99%